Análisis de viabilidad para implementar un sistema informático que facilite los procesos internos en el departamento de coordinación académica de la Facultad de Ciencias Sociales Jurídicas y de la Educación de la Universidad Técnica de Babahoyo - Samaniego Torres, Irene Isabel (2020)
The present case study is a feasibility analysis for the implementation of a computer system that streamlines the internal processes of the academic coordination department of the Faculty of Legal Social Sciences and Education of the Technical University of Babahoyo. During the investigation and investigation of the case, it is necessary to determine the feasibility of the computer system, since although it has a relatively similar definition, a project may be feasible but not viable, the document answers several questions that arose in the field research that was carried out. Consequently, analyzing the responses, it was determined that the implementation would have many benefits in that department.